# Solve for n -15=-(3n)/5

-15=-3n5
Rewrite the equation as -3n5=-15.
-3n5=-15
Multiply both sides of the equation by -53.
-53⋅(-3n5)=-53⋅-15
Simplify both sides of the equation.
Simplify -53⋅(-3n5).
Cancel the common factor of 5.
Move the leading negative in -53 into the numerator.
-53⋅(-3n5)=-53⋅-15
Move the leading negative in -3n5 into the numerator.
-53⋅-3n5=-53⋅-15
Factor 5 out of -5.
5(-1)3⋅-3n5=-53⋅-15
Cancel the common factor.
5⋅-13⋅-3n5=-53⋅-15
Rewrite the expression.
-13⋅(-3n)=-53⋅-15
-13⋅(-3n)=-53⋅-15
Cancel the common factor of 3.
Factor 3 out of -3n.
-13⋅(3(-n))=-53⋅-15
Cancel the common factor.
-13⋅(3(-n))=-53⋅-15
Rewrite the expression.
-1⋅(-n)=-53⋅-15
-1⋅(-n)=-53⋅-15
Multiply.
Multiply -1 by -1.
1⋅n=-53⋅-15
Multiply n by 1.
n=-53⋅-15
n=-53⋅-15
n=-53⋅-15
Simplify -53⋅-15.
Cancel the common factor of 3.
Move the leading negative in -53 into the numerator.
n=-53⋅-15
Factor 3 out of -15.
n=-53⋅(3(-5))
Cancel the common factor.
n=-53⋅(3⋅-5)
Rewrite the expression.
n=-5⋅-5
n=-5⋅-5
Multiply -5 by -5.
n=25
n=25
n=25
Solve for n -15=-(3n)/5

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top